2019
DOI: 10.1016/j.tim.2018.09.009
|View full text |Cite
|
Sign up to set email alerts
|

SAMHD1 Suppression of Antiviral Immune Responses

Abstract: SAMHD1 is a host triphosphohydrolase that degrades intracellular deoxynucleoside triphosphates (dNTPs) to a lower level that restricts viral DNA synthesis, and thus prevents replication of diverse viruses in non-dividing cells. Recent progress indicates that SAMHD1 negatively regulates antiviral innate immune responses and inflammation through interacting with various key proteins in immune signaling and DNA damage repair pathways. SAMHD1 can also modulate antibody production in adaptive immune responses. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 115 publications
2
35
0
Order By: Relevance
“…In this context, the fact that SAMHD1-mediated restriction of exogenous DNA expression does not involve interferon may be additionally beneficial and protects the host from frequent stimulation by interferons. In fact, SAMHD1 has been reported to prevent type I interferon induction [1,10,11]. On the other hand, SAMHD1 expression can be stimulated by interferons [5,44], which might reflect a complexed crosstalk between interferon-dependent and -independent pathways that restrict exogenous DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the fact that SAMHD1-mediated restriction of exogenous DNA expression does not involve interferon may be additionally beneficial and protects the host from frequent stimulation by interferons. In fact, SAMHD1 has been reported to prevent type I interferon induction [1,10,11]. On the other hand, SAMHD1 expression can be stimulated by interferons [5,44], which might reflect a complexed crosstalk between interferon-dependent and -independent pathways that restrict exogenous DNA.…”
Section: Discussionmentioning
confidence: 99%
“…SAMHD1 (Sterile Alpha Motif and Histidine-aspartate Domain containing protein 1) is expressed in both cycling and noncycling cells, and has been documented as a host restriction factor in the intrinsic antiviral immune system [1]. It possesses a triphosphohydrolase activity that catalyzes the conversion of deoxyribonucleoside triphosphates (dNTP) to deoxyribonucleosides (dN) and triphosphates [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it was also found that SAMHD1 is a key regulator in innate immune sensing [72][73][74]. SAMHD1 can prevent the cytosolic accumulation of ssDNA by promoting the degradation of nascent DNA at stalled replication forks, which may escape the nucleus during mitosis, thereby limiting innate immune sensing by cGAS [73]. Another study reported that SAMHD1 is able to directly interact with the inhibitor-κB kinase ε (IKKε) and IRF7 to suppress the innate immune response by reducing IKKε-mediated IRF7 phosphorylation [72,74].…”
Section: Innate Control Of Cytoplasmic Dna Accumulationmentioning
confidence: 99%
“…Initially, SAMHD1 was discovered as a restriction factor that prevents HIV-1 reverse transcription through depletion of cellular dNTPs in myeloid cells [18,19]. More recently, it was also found that SAMHD1 is a key regulator in innate immune sensing [72][73][74]. SAMHD1 can prevent the cytosolic accumulation of ssDNA by promoting the degradation of nascent DNA at stalled replication forks, which may escape the nucleus during mitosis, thereby limiting innate immune sensing by cGAS [73].…”
Section: Innate Control Of Cytoplasmic Dna Accumulationmentioning
confidence: 99%
“…SAMHD1 is a triphosphohydrolase (dNTPase) enzyme, which regulates intracellular levels of dNTPs and acts as an intrinsic immune response factor (11, 12). To function as a dNTPase, the protein forms a homo-tetramer, which is destabilized by phosphorylation.…”
Section: Introductionmentioning
confidence: 99%